PENDAMPINGAN DAN PELATIHAN DIVERSIFIKASI PRODUK PENGOLAHAN IKAN BAGI WANITA NELAYAN PESISIR KUPANG - Yoga Salean, Debryana; Nursiani, Ni Putu; Fanggidae, Rolland E; Helvinda Lada, Jachielin (Transpublika Publisher, 2023)
The purpose of this service is to carry out mentoring and training on the innovation of processed fish products in Tablolong village in West Kupang District, related to the development of new processed fish products and business planning for the Tablolong village community. West Kupang sub-district was chosen because the villages in it have potential natural resources (plantations, fisheries, agriculture, tourism) that can be optimized to increase village independence. This service is a university response to encourage the growth of young entrepreneurs in the village. Intensive assistance is sought to ensure that product innovation development efforts can be implemented effectively and can at least contribute to the economy of Tablolong village, West Kupang sub-district. Ultimately, the village community is expected to implement the business idea in order to produce young village entrepreneurs who contribute to the economic development of the village.